Хазары и Византия: первые контакты - Цукерман, К. (Материалы по археологии, истории и этнографии Таврии, 2001)
Византийская империя и Хазарский каганат выступают совместно на арене истории на протяжении примерно трех веков, и связи между обоими государствами были изначально очень тесны When and whence did the Khazars first arrive in the Caspian and the Pontic steppe? The debate is old and the dates proposed vary considerably. Many scholars admit nowadays that the references to sixth-century Khazar raids on Byzantium and Persia figure in very late sources and are of dubious value. They rather focus instead on the evidence of the Khazar participation in Heraclius’ campaign against Persia in the late 630s. The evidence appears so overwhelming that this episode is described in a recent book as the “naissance officielle” of the Khazar people. This article proposes a comprehensive study of the main source cited in support of this view, which are the seventh-century chapters of the History of Caucasian Albania by Movses Dasxuranc’i. A new analysis of the sources used by Movses supports the identification of Heraclius’ allies as Turks and eliminates the Khazars from the picture. A re-examination of another contemporary source, the Armenian Geography, suggests that the Khazars did not come anywhere close to the Caspian before the 660-670s. What is more, the country of Barsilia, from which the Khazars emerged on the way to their first conquests, is shown to be located not in the interfluvium of Sulak and Terek, where it is most often situated by scholars, but about 1000 km to the north, on the Volga, in the region of the Samara Elbow.